Deposition of thick Si coating with low residual stress on SiC ceramics by fabricating multilayer with compressive/tensile stress layer-pairs. (5th October 2016) - Yang, Yong; Zhang, Junwei; Fu, Chaoli; Liu, Guiling; Liu, Yan; Yao, Xiumin; Liu, Xuejian; Chen, Zhongming; Huang, Zhengren
Abstract: Surface modification can significantly improve surface properties of lightweight SiC ceramics as optical component for Large Space Optical Telescope. Usually, thick Si-modified coatings can be applied to cover surface defects and decrease polishing cost/time of SiC ceramics. However, it is one great challenge for depositing thick Si-coating with low residual stress on large-scale SiC ceramics by physical vapor deposition (PVD) method because too large residual stress often leads to the stress cracking of thick coatings. Here, silicon multilayer with alternate compressive/tensile stress layer pairs was designed and deposited alternately onto SiC substrates in order to prepare thick Si-coatings with low residual stresses. The silicon multilayer with compressive/tensile stress pairs were obtained by plasma ion assisted deposition and electron beam physical vapor deposition, respectively. The total thickness of as-deposited Si-multilayer can reach as much as 20 μm. Remarkably, the residual stress of silicon-multilayer tends to be negligible. Meanwhile, thick Si-coating bonds tightly with SiC substrate, and shows ultra-flat mirror surface with surface roughness of 0.69 nm RMS after polishing. It is demonstrated that silicon multilayer with low residual stress is a promising way to realize surface modification of SiC ceramics for optical mirror application. Graphical abstract: Highlights: Si multilayer coatings with alternate compressive/tensile stress layer pairs exhibit low residual stresses. The thickness of Si multilayer coatings can reach 20 μm. Si-modified SiC ceramics exhibit ultra-flat mirror surface with surface Roughness of 0.69 nm after polishing.